하이브리드 코팅 시스템으로 제조된 초고경도 Cr-Si-C-N 나노복합 코팅막의 미세구조 및 기계적 특성 - 장철식(Chul Sik Jang); 허수정(Su Jeong Heo); 송풍근(Pung Keun Song); 김광호(Kwang Ho Kim) (Biuletyn Uniejowski, 2005)
Cr-Si-C-N coatings were deposited on steel substrate (SKD 11) by a hybrid system of arc ion plating (AIP) and sputtering techniques. From XRD, XPS, and HRTEM analyses, it was found that Cr-Si-C-N had a fine composite microstructure comprising nano-sized crystallites of Cr(C, N) well distributed in the amorphous phase of $Si_3N_4/SiC$ mixture. Microhardness of Cr(C, N) coatings and Cr-Si-N coatings were reported about $\~22 GPa$ and $\~35 GPa$, respectively. As the Si was incorporated into Cr(C, N) coatings, The Cr-Si-C-N coatings having a Si content of $9.2 at.%$ showed the maximum hardness value. As increased beyond Si content of $9.2 at.%$, the interaction between nanocrystallites and amorphous phase was gone, the hardness was reduced as dependent on amorphous phase of $Si_3N_4/SiC$. In addition, the average coefficient of Cr-Si-C-N coatings largely decreased compared with Cr(C, N) coatings.